Retinal Vessel Diameters and Physical Activity in Patients With Mild to Moderate Rheumatic Disease Without Cardiovascular Comorbidities - Deiseroth, Arne; Marcin, Thimo; Berger, Colette; Infanger, Denis; Schäfer, Juliane; Bannert, Bettina; Schmidt-Trucksäss, Arno; Voll, Reinhard E.; Kyburz, Diego; Hanssen, Henner (Frontiers in Physiology, 2018)
Objectives: Low-grade systemic inflammation is responsible for atherosclerotic lesions in patients with rheumatic diseases. Vascular dysfunction is a precursor of atherosclerosis and can be improved by physical activity (PA). Our aim was to asses micro- and macrovascular function as well as PA and cardiorespiratory fitness (CRF) in patients with rheumatic diseases in the absence of cardiovascular (CV) comorbidities compared to controls. Methods: Fifty-one patients without CV comorbidities were compared to 35 controls. Retinal microvascular diameters were assessed using a Retinal Vessel Analyzer. Arterial stiffness (AST) was measured by applanation tonometry. CRF was assessed as peak oxygen consumption and PA was assessed with a questionnaire. Results: Retinal venular diameters were significantly wider in patients [median 221 μm (interquartile range (IQR) 211, 231)] compared to controls [median 215 μm (IQR 196, 223); p = 0.01]. One hour increase of PA per week led to a venular constriction of −0.56 μm (95%CI −1.09, −0.03; p = 0.04). In our patients with low disease activity (median DAS28 1.9; median BASDAI 2.8), no differences in AST were evident compared to controls. The association of PA and CRF with AST was not independent of blood pressure. Conclusions: Patients with rheumatic disease and mild-to-moderate disease activity show an impairment of the retinal microvasculature but not of large artery stiffness. Retinal vessel analysis seems to be a sensitive biomarker to unmask vascular impairments even in the absence of classic CV risk factors. PA may have the potential to counteract the development of small artery disease at early stages of rheumatic disease.